Antimicrobial and Synergistic Activity of 2,2′,4-Trihydroxybenzophenone Against Bacterial Pathogens of Poultry - Aranda, Martha Isabel Realpe; Gómez, Gabriel Andres Tafur; de Barros, Mariana; dos Santos, Marcelo Henrique; de Oliveira, Leandro Licursi; Pena, Junnia Luisa; Moreira, Maria Aparecida Scatamburlo (Frontiers in Microbiology, 2019)
In poultry farming, the spread of bacterial pathogens results in disease outbreaks causing significant economic losses to this industry. Many of these pathogenic bacteria are zoonotic and have a substantial impact on public health. Antimicrobials are essential for the prevention and treatment of these bacterial infections. However, the indiscriminate use of these agents provides favorable conditions for selection, propagation and persistence of bacteria and development of antimicrobial resistance. We developed a new antimicrobial candidate that could be used alone or in synergism to research protocols for therapeutic, prophylactic and growth promoter uses to poultry industry. The present study aimed at evaluating the antimicrobial activity of the synthetic compound 2,2',4-trihydroxybenzophenone against pathogenic bacteria that cause important diseases in poultry and public health. We tested the hemolytic effect of this compound, studied its synergistic effect with conventional antimicrobials and analyzed the site of action on the bacteria. The results of our study showed antimicrobial activity of benzophenone against Gram-positive and Gram-negative bacteria with similar effect in ATCC (American type culture collection) and field isolates. This compound was non-hemolytic. 2,2',4-trihydroxybenzophenone acted on the bacterial cell wall. We identified the synergistic effect between 2,2',4-trihydroxybenzophenone and bacitracin, this effect indicate that antimicrobial synergism may be useful for the treatment of necrotic enteritis in poultry. This compound may also be used as a growth promoter by reducing the dose of bacitracin and thus decreasing the pressure of bacterial resistance in poultry which would avoid the development of cross-resistance in humans.